PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PERSEPSI NILAI DAN PENGALAMAN TERHADAP NIAT MEMBELI KEMBALI (Studi kasus pada Toyota Avanza di Kota Denpasar) - Shantika, Ketut Adi Ananta; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 8 No 6 (2019)DO - 10.24843/EJMUNUD.2019.v08.i06.p22, 2019)
Company should consider some factors affects repurchase intention, to increase company’s income. Goal of this research is to knowing the effect of perceived value, experience and customer satisfaction as a cause factor to the repurchase intention. This research applied in automotive product, with brand Toyota Avanza in Denpasar City, Bali – Indonesia. Sample used are 124 respondents, with non-probability method, especially purposive sampling. Data collection did by giving questionnaire through offline and online. Analytic techniques used are Partial Least Square and Sobel Test to testing the mediating effect. Based on this analysis, found that perceived value, experience, and customer satisfaction significantly and positively affects repurchase intention directly, beside that perceived value and experience indirectly affects repurchase intention through customer satisfaction as a mediator. This results shows, better perceived value has by the costumers, better customers’ experiences, better customer satisfaction could increase the intention to repurchase in the future for the same product. This research implies, Toyota-Astra Motor company should adding luxury value to Toyota Avanza, redesigning interior and exterior had by Toyota Avanza, and add some features that can increasing the customers’ intention to repurchasing Toyota Avanza in Denpasar City at the future.